Effectiveness of Shipping Routes through Public Service Obligation for PT Pelni (PERSERO) - Fildzah Ibah Thoyybah; Romy Chandra; Ryansyah Mujizat Hakim; Alexandros Siringo Ringo (Meteor STIP Marunda, 2024)
PT Pelayaran Nasional Indonesia (PT PELNI) has faced criticism for inefficiencies and ineffectiveness in its utilization of Public Service Obligation (PSO) funds, which are often diverted from their primary purpose of improving passenger transport services. This misallocation has exacerbated infrastructure disparities, particularly in remote areas, regions with weaker economies, and routes managed by operators incurring losses. Such gaps present significant challenges to achieving equitable access to maritime transportation. As stipulated in Law No. 17 of 2008, the shipping system encompasses waterborne transportation, ports, safety, security, and marine environmental protection, all of which significantly influence the mobility of people and goods. However, service quality perceptions vary across different socio-economic groups, highlighting the need for targeted improvements. This study evaluates the effectiveness of PSO implementation at PT PELNI, focusing on optimizing subsidized shipping routes to enhance service delivery and contribute to regional economic development. The findings aim to inform policymakers and stakeholders in improving PSO administration and maritime infrastructure.